Conservation agriculture enhances maize yields and profitability in Mexico’s semi-arid highlands - Abel Saldivia-Tejeda; Miguel Ángel Uribe-Guerrero; Juan Manuel Rojas-Cruz; Ouorou Ganni Mariel Guera; Nele Verhulst; Simon Fonteyne (Scientific Reports)
Abstract Rainfed agriculture in semi-arid regions is affected by variable rainfall patterns, resulting in low yields under conventional farming systems. To address this issue, cropping systems based on conservation agriculture were evaluated in 2 field experiments on 17 farmers’ fields in the semi-arid highlands of Queretaro, Mexico, from 2013 to 2020, to assess yields and profitability. Monocropped maize (Zea mays L.) under conventional tillage was compared to growing maize on permanent beds with soil mulch, either monocropped or in rotation with triticale (X Triticum Secale Wittmack), oats (Avena sativa L.), or common beans (Phaseolus vulgaris L.). In the San Juan del Rio field experiment, maize yields on permanent beds averaged from 2,475 to 3,517 kg ha− 1 over five years, exceeding 70% the yields under conventional tillage. In the Cadereyta field experiment, 4-year average maize yields on permanent beds ranged from 979 to 1,382 kg ha− 1 with no significant difference to those under conventional tillage. In farmers’ fields, maize on permanent beds yielded an average of 3,717 kg ha− 1, 70% higher than with conventional tillage. The most profitable system was permanent beds with a maize-bean rotation in field experiments and with maize monocropping in farmers’ fields. Overall, conservation agriculture can improve maize yields and profitability in Central Mexico’s semi-arid highlands.